Code-Switching used by Putri Tanjung and Boy William in Ngobrol Sore Semaunya’s Episode 2 - Sitti Azyizah; Dewi Nuryanti (Talenta Publisher, 2023)
This study wants to investigate the code-switching that occurred in the PodcastNgobrol Sore Semaunya’s Podcast Episode 2. This study also aims to describe the types ofcode-switching, the factors causing the code-switching, and the function of code-switchingthat occurred in the Podcast Ngobrol Sore Semaunya Episode 2. This study used qualitativedescriptive research. The object of this research is a data containing code-switching inspeech events on the Podcast Ngobrol Sore Semaunya Episode 2. The result showed threeresults. The first type of code-switching that occurs according to Stockwell (2007) thereare, 1) tag-switching, 2) intra-sentential switching, 3) inter-sentential switching. Second, thereason that causes code-switching according to Hoffman (1991), there are 1) talking aboutparticular topic, 2) quoting somebody else, 3) express solidarity, 4) interjection, 5)repetition used for clarification, 6) intention of clarifying the speech content for theinterlocutor and, 7) expressing group identity. The last is the code-switching functionaccording to Gumperz (1982), there are 1) quotation, 2) addressee specification, 3)interjection or sentence filler, 4) reiteration, 5) message qualification, and 6) objectification.